2018
DOI: 10.1016/j.jrp.2018.09.003
|View full text |Cite
|
Sign up to set email alerts
|

HEXACO personality predicts counterproductive work behavior and organizational citizenship behavior in low-stakes and job applicant contexts

Abstract: This study examined the degree to which the predictive validity of personality declines in job applicant settings. Participants completed the 200-item HEXACO Personality Inventory-Revised, either as part of confidential research (347 nonapplicants) or an actual job application (260 job applicants). Approximately 18months later, participants completed a confidential survey measuring organizational citizenship behavior (OCB) and counterproductive work behavior (CWB). There was evidence for a small drop in predic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 70 publications
2
42
0
1
Order By: Relevance
“…We don't doubt the replicability of the results reported by Biderman et al (2018Biderman et al ( , 2019, see also Anglim, Morse, De Vries, MacCann, & Marty, 2017;Anglim, Lievens, Everton, Grant, & Marty, 2018), but we do question the interpretation of their evaluation factor as primarily a substantive personality dimension. To explain, we first describe Biderman et al's bifactor ESEM approach, in which an eight-factor solution (or a seven-factor solution if the analysis involved the Big Five inventories) was rotated to a target rotation matrix.…”
Section: Childers Johnson Mcabee and Bidermanmentioning
confidence: 60%
“…We don't doubt the replicability of the results reported by Biderman et al (2018Biderman et al ( , 2019, see also Anglim, Morse, De Vries, MacCann, & Marty, 2017;Anglim, Lievens, Everton, Grant, & Marty, 2018), but we do question the interpretation of their evaluation factor as primarily a substantive personality dimension. To explain, we first describe Biderman et al's bifactor ESEM approach, in which an eight-factor solution (or a seven-factor solution if the analysis involved the Big Five inventories) was rotated to a target rotation matrix.…”
Section: Childers Johnson Mcabee and Bidermanmentioning
confidence: 60%
“…Whereas, some studies have found that OCB-I and OCB-O are predicted equally well by Conscientiousness, and Agreeableness (being kind, sympathetic, warm; Chiaburu et al, 2011;Judge et al, 2013), other results suggest that OCB-I is best predicted by Agreeableness and OCB-O is best predicted by Conscientiousness (Ilies et al, 2009). Despite the relevance of OCB for organizations, there exist only a few studies on its relationship with personality in selection research (Anglim et al, 2018;Heimann et al, 2020).…”
Section: Personality and Performancementioning
confidence: 99%
“…Going beyond the traditional Big Five personality traits, Honesty-Humility has been shown to explain a significant proportion of variance in CWB over and above the other personality traits (Pletzer et al, 2019). Despite its harm to organizational success (Berry et al, 2007), CWB has rarely been considered as a criterion in selection research (Dilchert et al, 2007;Anglim et al, 2018).…”
Section: Personality and Performancementioning
confidence: 99%
“…Conscientiousness being predictive of OCB in Blickle et al, 2009; versus Adjustment, Prudence, and Ambition being predictive of OCB in Hogan et al, 1998;versus Agreeableness and Extraversion being predictive of OCB in Anglim et al, 2018). Specifically, in the selection context, exploring methods other than self-reports might offer a promising opportunity to improve personality assessment and thereby the pinpoint prediction of different OCBs.…”
Section: Ocb As a Criterion In Personnel Selectionmentioning
confidence: 99%